Dielectrophoretic-Field Flow Fractionation Analysis of Dielectric, Density and Deformability Characteristics of Cells and Particles - Gascoyne, Peter R.C. (2009)
Dielectrophoretic field-flow fractionation (DEP-FFF) has been used to discriminate between particles and cells based on their dielectric and density properties. However, hydrodynamic lift forces (HDLF) at flow rates needed for rapid separations were not accounted for in the previous theoretical treatment of the approach. Furthermore, no method was developed to isolate particle or cell physical characteristics directly from DEP-FFF elution data. An extended theory of DEP-FFF is presented that accounts for HDLF. Using DS19 erythroleukemia cells as model particles with frequency-dependent dielectric properties, it is shown that the revised theory accounts for DEP-FFF elution behavior over a wide range of conditions and is consistent with sedimentation-FFF when the DEP force is zero. Conducting four elution runs under specified conditions, the theory allows for the derivation of the cell density distribution and provides good estimates of the distributions of the dielectric properties of the cells and their deformability characteristics that affect HDLF. The approach allows for rapid profiling of the biophysical properties of cells, the identification and characterization of subpopulations and the design of optimal DEP-FFF separation conditions. The extended DEP-FFF theory is widely applicable and the parameter measurement methods may be adapted easily to other types of particles.